Optical Investigation of Proton‐Irradiated Metal Organic Chemical Vapor Deposition AlGaN/GaN High‐Electron‐Mobility Transistor Structures. Issue 4 (18th February 2020) - Freitas, Jaime A.; Weaver, Bradley D.; Koehler, Andrew D.; Gallagher, James C.; Anderson, Travis J.
Abstract : About 2 MeV proton numerical calculation damage indicates that a quasiflat profile is introduced into the GaN buffer layer of high‐electron‐mobility transistor (HEMT) templates. A previous transport study of such HEMT structures showed increased breakdown voltage and reduced GaN buffer layer leakage after proton irradiation. Hyperspectral electroluminescence measurements detected the emission band in the spectral region between 700 and 800 nm. This emission is assumed to be associated with the generation of trap levels responsible for the device failure. To obtain insights into the nature of radiation‐generated traps, detailed low‐temperature photoluminescence (PL) and cathodoluminescence (CL) experiments are conducted in a set of virgin and proton‐irradiated device structure templates. Both the PL and CL spectra show large intensity variations of all emission bands, in the spectral range between 330 and 890 nm, with increasing proton dosage. This is consistent with the introduction of compensating and/or nonradiative recombination centers in the GaN buffer layer. Luminescence measurements carried out under various excitation conditions show different recombination rates for emission bands observed near 420 and 550 nm, indicating different free carrier capture rates. Spectral analysis suggests that these two emission bands have different dependences on proton irradiation dosage, consistent with different chemical natures. Abstract : What is the mechanism associated with radiation‐induced damage in GaN high‐electron‐mobility transistors? The numerical calculation damage indicates that a quasiflat profile is introduced into the GaN device buffer layer. Depth profiling luminescence measurements show large spectral intensity variations, increasing with increasing irradiation dosage, consistent with the introduction of radiative and nonradiative carrier trap centers in the GaN buffer layer.